Sewing accessories at home & on the go - Mueller, Jamie; Rimes, jill (Chicago Annie's, 2013)
If one has always wanted to organize ones sewing room, this book will help do just that! Whether one has a tiny sewing space in the corner of a room or a dedicated space that is all theirs to spread out ones sewing projects, one will find organizers in this book that will fit all needs. Stitch up the Cool Watermellon Pincushion to keep track of pins. Or stitch up the Hanging Ruler Organizer. It's a great project to get rulers up off the sewing table and tucked nicely into a space-saving wall hanger
2
Keywords: CRAFTS & HOBBIES -- Sewing; FAMILY & RELATIONSHIPS -- General; Sewing